Levantamento de mapas operacionais de transferência metálica para soldagem MIG/MAG de aço ao carbono na posição plana - Souza, Daniel (2010)
The MIG/MAG process is nowadays the most important welding process. This is due to its high production capacity, characteristic searched by industries to improve their manufacturing processes. Thus, due to this process relevance, development of tools that helps to understanding how it works comes out as necessary, especially in relation to proper welding setting up. One tool for this task is the transfer mode map, which predicts the type of metal transfer according to the welding setting up. However, these maps, normally, are more scientific oriented rather that for practical purposes. In this context, the objective of this work was to map the transfer modes in such a way that welders, supervisors and engineers could be helped in the choice of the best setting up needed. For this purpose, a methodology was developed to provide more information than transfer modes according to the parameter setting up. The proposed mapping had the intention of obtaining transfer regions with proper operating characteristics (stable transfer resulting of appropriate welding conditions) and also information about weld bead conditions, production, thermal cycle and arc radiation. For each transfer mode looked for working at typical welding conditions, which mean that the contact tip-to-work distance was different for the two main transfer modes (short-circuit and spray). A large number of experiments was performed to map the transfers, with the objective to determine a stable operating regions of short-circuit and spray transfer mode using the ER70S-6 welding wire with three different shielding gases. After mapping, single-welded butt joint were carried-out using specific points of the maps instead of bead-on-plate. The proposed methodology was efficient in exterminating regions of operational stability, according to the experiments. It was also possible to have better welding geometries, in general, for setting ups within the map region of operational stability, but the results also depend on the shielding gas and the transfer mode. For setting ups outside the map region of operational stability the bead finish gets worse, except for spray transfer mode when working below the region of operational stability. The deposition efficiency is lower for setting ups outside the region and with gases containing higher levels of CO2, except for short-circuit transfer. The arc radiation intensity is lower in regions below the operational stability and higher above this position, but it is highly dependent of the arc length. Changes in the contact tip-to-work distance and/or in the power source inductance have no influence on the region of operational stability, except for short-circuit transfer, in which the contact tip-to-work distance is able to reduce the set voltage for this region.